When a Good Science Base is not enough to Create Competitive Industries: Lock-in and Inertia in Russian Systems of Innovation. - Narula, R; Jormanainen, I (SLPTMD (Department of International Development, University of Oxford), 2008)
Despite having a formidable position in terms of domestic R&D; activity and a welldeveloped science and technology infrastructure prior to transition, Russia has failed to create a competitive firm sector. Using a systems of innovation approach, we argue that institutions are subject to inertia when political and economic regimes were rapidly reformed, and the system structural lock-in, causing industrial enterprises to engage in routines that generated a sub-optimal outcome. Market forces did not result in the western style model, but a hybrid one. A significant segment of industry maintains a Soviet-style dependence on ‘top-down’ supply-driven allocation of resources and a reliance on external (and domestic) network of sources for innovation and capital. At the same time, ‘new’ industries have also evolved which undertake their own R&D;, and utilise foreign sources of capital and technology, and at least partly determine their production and innovative activities on the basis on market forces.